Angina bullosa hemorrhagica: a case report - Molano-Valencia, Pablo Emilio; Luna-Otálora, Sergio; Vásquez-Valencia, Mauricio Andrés (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Angina bullosa hemorrhagica (ABH) was first described by Badham in 1967 as a disease characterized by either one single lesion or multiple lesions of sudden appearance, with a color ranging from dark red to purple. It often affects the soft palate, but there are reports of cases in the oral mucosa, the side edge of the tongue, and the gingiva following hygienic therapy. This report presents the case of a patient subjected to crown enlargement surgery to correct type 1B altered passive eruption. Two weeks after surgery she had a red painful lesion of sudden appearance in the vestibular gingiva of the upper left and right maxillary, that worsened in a period of four months. A biopsy was taken, with results compatible with ABH. The goal of this article is to report a new case of ABH, its clinical characteristics and differentiation to other hemorrhagic diseases of the oral cavity, as well as its respective management